Properties of Self-Compacting Concrete with Recycled Coarse Aggregate - W. C. Tang; P. C. Ryan; H. Z. Cui; W. Liao (Advances in Materials Science and Engineering)
The utilisation of recycled concrete aggregate (RCA) in Self-Compacting Concrete (SCC) has the potential to reduce both the environmental impact and financial cost associated with this increasingly popular concrete type. However, to date limited research exists exploring the use of coarse RCA in SCC. The work presented in this paper seeks to build on the existing knowledge in this area by examining the workability, strength, and fracture properties of SCCs containing 0%, 25%, 50%, 75%, and 100% coarse RCA. The experimental programme indicated that at RCA utilisation levels of 25% to 50% little or no negative impact was observed for strength, workability, or fracture properties, with the exception of a slight reduction in Young’s modulus.